2018
DOI: 10.1002/etc.4296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Cr(III) accumulation, biomass production, and phenolic profile in 2 Salvinia species

Abstract: We analyzed the effect of pH on Cr(III) accumulation, biomass production, and phenolic profile of Salvinia rotundifolia and Salvinia minima plants grown in the presence of increasing concentrations of CrCl3. Biomass accumulation, metal tolerance index, and photosynthetic pigment contents indicate that Salvinia rotundifolia seems to be more tolerant of Cr(III) than S. minima at different pHs. Increased metal accumulation by Salvinia species under increasing pH could be explained by changes of the protonation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…The metal accumulation values in the tissue of S. auriculata measured in this study are lower than those reported by Espinoza-Quiñones et al, who exposed S. auriculata to concentrations of 5 mg/L Cr(III) in a hydroponic solution, obtaining an accumulation of 10.12 and 2.08 mg/g in root and leaf tissue, respectively, after 7 days [32]. Conversely, Ponce et al measured Cr(III) concentrations in Salvinia rotundifolia in different structures and found that 0.8 mg/g accumulated in fronds and 1.3 mg/g in laciniae, at pH 6 and a concentration of 20 mg/L Cr(III), conditions similar to those of our study [33]. In E. crassipes, BAF values for leaves were 37 ± 12 and 21 ± 6, while in roots, they were 1.2264 ± 35 and 326 ± 93 for concentrations of 2 and 20 mg/L of Cr(III), respectively.…”
Section: Removal and Accumulation Of Chromium (Iii) In Nutrient Solut...supporting
confidence: 89%
See 1 more Smart Citation
“…The metal accumulation values in the tissue of S. auriculata measured in this study are lower than those reported by Espinoza-Quiñones et al, who exposed S. auriculata to concentrations of 5 mg/L Cr(III) in a hydroponic solution, obtaining an accumulation of 10.12 and 2.08 mg/g in root and leaf tissue, respectively, after 7 days [32]. Conversely, Ponce et al measured Cr(III) concentrations in Salvinia rotundifolia in different structures and found that 0.8 mg/g accumulated in fronds and 1.3 mg/g in laciniae, at pH 6 and a concentration of 20 mg/L Cr(III), conditions similar to those of our study [33]. In E. crassipes, BAF values for leaves were 37 ± 12 and 21 ± 6, while in roots, they were 1.2264 ± 35 and 326 ± 93 for concentrations of 2 and 20 mg/L of Cr(III), respectively.…”
Section: Removal and Accumulation Of Chromium (Iii) In Nutrient Solut...supporting
confidence: 89%
“…E. crassipes can be used to treat urban leachates [ 28 ], in cyanide removal [ 29 ], and the treatment and removal of chromium in tannery effluents [ 30 ]. S. auriculata can remove heavy metals in a solution since this macrophyte has the ability to accumulate mercury in roots and tissues [ 31 ] and remove Cr(III) and Cr(VI) in hydroponic solutions [ 32 , 33 ]. Other species of the Salvinia genus have been extensively studied in metal phytoremediation.…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that accumulation of phenolic compounds in leaves and roots are mainly due to oxidative polymerization of enzymes involved in phenylpropanoid pathway that further alters the permeability of cell wall [81]. The most possible mechanism involved behind the microbe-mediated stimulation of phenolic compounds in the present study is that microbes actively participate in shikimate pathway of phenol biosynthesis during stressed conditions [82]. The microbes regulate phenol metabolism by generation of shikimic acid, a vital metabolite in phenol biosynthesis that in turn further generates and accumulates chorismic acid, the end product of shikimate pathway [76] Moreover, an upregulation in the expression levels of genes encoding different metabolites have also been measured through qRT-PCR in our previous studies [31].…”
Section: Discussionmentioning
confidence: 84%
“…The Cr(VI) reduction ability of fecal bacteria was determined as our previous study 6 with minor modifications that using YCFA medium 72 . After that, the supernatant was oxidized from Cr(III) to Cr(VI) using KMnO 4 73 to ensure the correctness of bacterial reduction.…”
Section: Methodsmentioning
confidence: 99%